Legal Analysis Regarding The Implementation of The Indonesian Game Rating System (IGRS) in The Protection of Child Consumers in Indonesia - Achmad Hanif Avicenna Setiady; Andriyanto Adhi Nugroho (Dinasti Research, 2026)
This study examines the implementation of the Indonesian Game Rating System (IGRS) within Indonesia's legal framework, focusing on child consumer protection in the digital gaming industry. Indonesia's rapidly expanding gaming market indeed generated economic benefits, but on the other hand, exposing children to age-inappropriate content at the same time. The Government responded by establishing the IGRS, a classification system based on age suitability and content descriptors, most recently revised through Minister of Communication and Digital Affairs Regulation No. 2 of 2024. Employing a normative legal method with statutory and conceptual approaches, this study analyzes relevant legislation, ministerial regulations, legal doctrine, and documented enforcement cases through descriptive-qualitative and teleological interpretation. The findings reveal that the IGRS remains structurally incomplete: it lacks a Government Regulation establishing binding enforcement, exhibits weak harmonization with Law No. 8 of 1999 on Consumer Protection, and relies on a self-classification model whose reliability was exposed by the 2026 Steam controversy. Enforcement in practice remains reactive, with no dedicated complaint mechanism for child consumers or their guardians. The study concludes that the IGRS has not yet achieved optimal legal protection for child consumers and recommends a comprehensive Government Regulation, an independent supervisory body, and accessible consumer redress mechanisms to strengthen Indonesia's digital game governance framework.